Perancangan Ulang Media Kampanye Event Street Race Polda Metro Jaya untuk Mengurangi Balap Liar Remaja - Tommi, Tommi; Naufaldi, Zidan Thoriq (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2023)
Among teenagers, the case of illegal racing is a phenomenon that often occurs. Illegal racing is an activity to compete with speed either by motorbike or by car which is carried out on public streets. The perpetrators of illegal racing are usually teenagers. They have a reason because of the lack of a place to channel their hobbies. So, they prefer to do it on the highway. Since the advent of the automotive trend among teenagers, many teenagers prefer to keep themselves busy with automotive hobbies, especially motorcycles, rather than doing brawls that are detrimental to society. But this hobby is also often misused. For example, for teenagers who have a hobby of drag racing, they often use public roads to carry out racing actions. In fact, there are also many teenagers with similar hobbies who use official racing arenas or what are commonly called circuits to channel their drag racing hobbies.